Pengawasan Terhadap Peredaran Kosmetik Yang TidakTerdaftar Di Badan Pengawasan Obat Dan Makanan Jawa Tengah - Cesyafrina; Esti Ningrum; Agoes Djatmiko (Wijayakusuma Law Review, 2021)
This study aims to determine the Consumer Protection Civil Servant Investigator (PPNS-PK) on the distribution of cosmetics thatare not registered at the Food and Drug Supervisory Agency (BPOM) Central Java, to find out the Constraints of ConsumerProtection Civil Servant Investigators (PPNS-PK). PK) on the circulation of cosmetics that are not registered with the Food andDrug Supervisory Agency (BPOM) of Central Java, to find out the efforts of the Consumer Protection Civil Service Investigator(PPNS-PK) in overcoming the circulation of cosmetics that are not registered with the Food and Drug Administration (BPOM).BPOM) Central Java. The method used is normative juridical, namely legal research carried out by examining library materialsor data as basic materials for research to be carried out by tracing regulations and literature related to the problems studied.Research Results: The role of Civil Servant Investigators for Consumer Protection in supervising cosmetics that are not registeredwith the Food and Drug Supervisory Agency of Central Java, which is in accordance with article 59 paragraph (1)-(4) of Law no.8 of 1999 concerning Consumer Protection, Constraints of Consumer Protection Civil Servant Investigators in the circulation ofcosmetics are not registered with the Central Java Food and Drug Administration, namely business actors do not have clearaddresses for cyber patrol officers assistance, Civil Servant Investigator Efforts Consumer Protection in overcoming thecirculation of cosmetics that are not registered with the Food and Drug Supervisory Agency of Central Java, namely by providinga complaint channel through digital media.